POLYGAMY AS A RESPONSE TO REJECTION OF SEXUAL RELATIONS: A STUDY OF JEMBER RELIGIOUS COURT DECISION NUMBER 3066/PDT.G/2024/PA.JR, FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW - Muh Zulfikri; Yusdi Haq (Journal Analytica Islamica, 2026)
This study was prompted by the emergence of a case regarding permission for polygamy based on the grounds that the wife was unable to fulfill her biological obligations, as outlined in the Decision of the Jember Religious Court No. 3066/Pdt.G/2024/PA.Jr. This issue is important to examine because it relates to the construction of the judge’s reasoning in interpreting biological obligations within the household according to Islamic family law and positive law in Indonesia. This study aims to analyze the judge’s reasoning in granting permission for polygamy and to assess its consistency with the principles of Islamic family law. This study employs a normative legal research method using a case study approach through the analysis of court rulings, legislation, Islamic family law literature, and other relevant legal materials. The results indicate that the judge interprets the inability to fulfill biological obligations as part of the condition where a wife cannot perform her duties as stipulated in the Compilation of Islamic Law. However, this reason is not used as the sole basis but is considered alongside other requirements such as the wife’s consent, economic capacity, and readiness to act fairly. This study concludes that judges’ rulings have sought to integrate the principles of justice, public interest, and positive legal provisions into religious judicial practice, thereby contributing to the development of contemporary Islamic family law scholarship.